1999
DOI: 10.1291/hypres.22.261
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Blood Pressures Obtained Using Different Measurement Methods in the General Population of Ohasama, Japan.

Abstract: To examine the relationships between casual, ambulatory and home blood pressure measurements in the general population, these measurements were obtained in 1,695 of 3,744 subjects aged 20 yr or older in Ohasama, Japan. Of these 1,695 subjects, 1,207 measured their home blood pressure more than 14 times in each of the morning and evening (881 untreated subjects including normotensives and untreated hypertensives, 56.4 ± 11.5 yr of age; 326 treated subjects, 66.0 ± 9.2 yr of age). We analyzed data in these 1,207… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…The genotypic distribution of this gene in the present study was quite similar to that reported by Takami et al (15), indicating that the disparate results were not due to a population difference between northern and central Japan. However, differences in life-style may have played a role, since our study was conducted in a rural area (20,21) and that of Tamaki et al was performed in an urban area (15). In addition, our study had fewer subjects with ABP, and our analysis was made by including all vascular events together.…”
Section: Discussionmentioning
confidence: 99%
“…The genotypic distribution of this gene in the present study was quite similar to that reported by Takami et al (15), indicating that the disparate results were not due to a population difference between northern and central Japan. However, differences in life-style may have played a role, since our study was conducted in a rural area (20,21) and that of Tamaki et al was performed in an urban area (15). In addition, our study had fewer subjects with ABP, and our analysis was made by including all vascular events together.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the advancement and popularity of hospital-based, 24-hour, ambulatory BP monitoring devices as well as homebased self-monitoring devices, the importance of the use of ambulatory BP, especially those measurements taken at home have gained attention (1)(2)(3)(4)(5)(6)(7)(8). HBP obtained early in the morning at home by self-measurement is specifically highlighted as having a substantial impact on cardiovascular risk.…”
Section: State Of Bp Controlmentioning
confidence: 99%
“…Indeed, HBP obtained early in the morning has been shown to have a substantial impact on the awareness of cardiovascular risks (1)(2)(3)(4)(5). In addition, many clinical reports indicate a close association between BP in the early morning and the occurrence of cardiovascular events such as myocardial infarction, cerebral apoplexy or sudden death (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Eighty percent of households in this town attended the class, and public health nurses visited all of the remaining households to provide instruction on home BP measurement and to check whether they were able to measure their own BP correctly. These procedures were also described in detail in our previous manuscript (18,20). Subjects were asked to measure their BPs in the sitting position once every morning within 1 h after awaking and after more than 2 min of rest, and to record the measurements for 4 weeks.…”
Section: Hbp Measurementmentioning
confidence: 99%